Analisis Kemampuan Menulis Cerita Imajinasi pada Model Pembelajaran Problem Based Learning - Laily Zaitin Nukha; Cahyo Hasanudin; Sutrimah Sutrimah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Writing in an activity to express thoughts and feelings in writing and indirecly. Writing is generally divided into two typpes, namely scientific writing and creative writing. Imaginary stories are texts produced from creative thoughts to create a story. So an effective learning model is also needed to write stories. PBL is a learning model that encourages students to solve a problem contextually. This research step uses the theory Miles and Huberman using triangulation data validation. Most students are able to write the orientation, complication, and resolution sections well. This can be seen from the majority of students who succeeded in compiling a complete orientation, displaying the conflict clearly in the complication, and the resolution of students in writing the conflict in its entirety in the resolution section. This shows that problem based learning (PBL) is effective in helping students understand the structure of imaginary stories and developing creativity and critical thinking skills in writing.